STUDY OF THE ANTIMICROBIAL EFFECTS OF THE STEM BARK EXTRACTS OF PARKIA BIGLOBOSA (JACQ.) BENTH AGAINST STAPHYLOCOCCUS AUREUS - Millogo-KonÃ©, H. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Staphylococcus aureus causes many infectious diseases in human. In traditional medicine, the stem bark of Parkia biglobosa is used for the treatment of many infections. Extracts of the stem barks were tested against strains of Staphylococcus aureus collected from pus, blood, vaginal secretions, sperms and urine and also against a collection strain of Staphylococcus aureus as a positive control. To select the most effective extract, tests have been conducted with the decoction, prepared according to the traditional healer receipe, and extracts obtained with different solvents (dichloromethan, 70% aqueous ethanol, ethyl acetate, water). The results showed that the decoction was active against Staphylococcus aureus, thus justifying its use in the traditional medicine. The results also revealed that the 70% hydroalcoholic extract was more active than the decoction and that ethyl acetate extract also exerted strong inhibition against Staphylococcus aureus. The dichloromethane extract had no effect against the tested strains. Column chromatography of the ethanolic extract followed by thin layer chromatography led to the isolation of gallic acid. Gallic acid isolated from the ethanolic fraction showed strong inhibition but its effectiveness was lower than what was observed with the synthetic gallic acid. The chemical screening of all these extracts showed that the dichloromethane extract contains mainly sterols, triterpens and coumarins. It also showed that the aqueous, the hydroethanolic and the ethyl acetate extracts contain saponosides, anthracenosides, tannins, flavonoids, reducing compounds but in different proportions, justifying the differences in their respective anti – Staphylococcus activities.